Avaliando a interação por rastreamento de olhos em tarefas cotidianas dos usuários em computadores - BRITO, Luciana Lima (2022)
Interactions in a computational environment performed using alternatives to the traditional mouse and keyboard are unusual, however, researches in the field of unconventional interactions are growing day by day in computing. The interactions by eye tracking include the act of looking to the object’s region of interest on the screen and estimating the respective point of eye fixation, as well as using blink of the eyes to interact directly with these objects. In this work are evaluated the interactions using eye tracking in basic tasks of an user with a computer, using the file manager and a web browser. Tests of usability for the purpose of identifying the acceptability levels and the difficults found in the use of this kind of interaction with the proposed applications were done. The usability scenarios were evaluated by two specialists and performed with ten volunteers participants. For the results’ analysis were considered the time that each participant spent to conclude the tasks, the interaction errors and the particular considerations about the experience of each one. The results present participants very excited and receptive to the idea, but although they concluded the proposed tasks some difficults were found in the use of the eye tracker, for example, related to the blink ability to interact with objects, the use of eyeglasses, the environment setup, and others. Finaly, suggestions are made to improve the use of eye tracking, also considering the suggestions of the participants.